Association of the ABCB1 C3435T gene polymorphism (SNPs) with the response to neoadjuvant chemotherapy in women with breast cancer in northeastern Brazil - Bezerra, Diego de Aragão; Linhares, José Juvenal; Noronha, Emmanuelle Coelho; Tavares, Kaio César Simiano; Antunes, André Saraiva Leão Marcelo; Coelho, Regina Freitas; Marques, Marcos Vinícius Souza (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: breast cancer (BC) is the most common tumor and the leading cause of cancer-related death among the female population worldwide. Polymorphisms genetics of ABCB1 gene contributed to breast cancer susceptibility and interindividual differences in chemotherapy response. Objectives: to evaluate the association between the ABCB1 C3435T gene polymorphism (SNPs) with the response to neoadjuvant chemotherapy in women with breast cancer. Methodology: this study included 32 female patients who received neoadjuvant chemotherapy. The polymorphisms were genotyped through real-time allele-specific polymerase chain reaction (PCR). The statistical analysis was performed using the Fisher’s exact test or Pearson’s chi-square test in the Statistical Package for Social Sciences (SPSS) version 20.0 software. Results: the genotypes found for the C3435T polymorphism were in Hardy-Weinberg equilibrium and their genotypic distributions were CC= 10 (31.1%), CT= 14 (43.8%), and TT= 08 (25.0%) with χ2: 0.86 and p-value > 0.05. Allele frequencies were C = 0.54 and T = 0.46. There were no significant statistical differences between genotypes considering the response to neoadjuvant chemotherapy and immunohistochemistry; the presence of the T allele was associated with worsen axillary status response to neoadjuvant chemotherapy. Conclusion: no definite association between the presence of C3435T polymorphism and the response to neoadjuvant chemotherapy was observed. Further studies in Brazil involving larger samples will contribute to validating the results of this study.